PENGARUH UKURAN KOPERASI, JENIS KOPERASI SERTA PENGALAMAN KEPENGURUSAN MANAJEMEN TERHADAP KUALITAS SISTEM PENGENDALIAN INTERN PADA KOPERASI DI KABUPATEN TABANAN - Priliandani, Ni Made Intan; Juniariani, Ni Made Rai; Mariyatni, Ni Putu Sri (Jurnal Aplikasi Akuntansi, 2018)
Cooperatives are a different organization with other businesses, such as BUMN and BUMD or government organizations. The uniqueness of cooperatives is that cooperatives are business units that have multiple identities in which each cooperative member is the owner and user of cooperative services. In order to be able to compete with other financial institutions, the cooperative must be able to determine a policy and strategy that must be developed and improved. One policy that can be taken to assist the development of cooperatives is the effectiveness of management control systems. Internal control is an activity that is influenced by the organization, coordinated methods and provisions to maintain organizational wealth, check accuracy, and reliability of accounting data, to improve business efficiency and encourage compliance with company regulations. The cooperative internal control system is influenced by several factors, namely the size of the cooperative, the type of cooperative, and the management experience of management. This study has the purpose of 1) whether the size of the cooperative influences the quality of the internal control system in cooperatives in Tabanan Regency. 2) whether the type of cooperative influences the quality of the internal control system in cooperatives in Tabanan Regency. 3) whether the management experience affects the quality of the internal control system in cooperatives in Tabanan Regency. This study uses primary data in the form of answers to questionnaires from supervisors and directors of cooperatives in Tabanan district. The sampling technique in this study is purposive sampling technique so that the sample in this study amounted to 35 cooperatives. The analysis technique used to answer the hypothesis is multiple linear regression. The results of the study show that 1) the size of the cooperative has a positive effect on the quality of the internal control system. 2) types of cooperatives have a positive effect on the quality of the internal control system. 3) management management experience has a positive effect on the quality of the internal control system.